Reawakening the Past: The Role of Gamification in Preserving Cultural Legacy – A Case Study from Czechia - Petra Karvánková; Vojtěch Blažek; Renata Klufová; Jiří Rypl (Plural: History, Culture, Society)
In recent years, there has been a growing emphasis on protecting both natural and cultural heritage, which often faces the threat of being forgotten or lost. The digital era and new technologies have opened up new opportunities to make these heritage sites accessible to the public. This trend is particularly evident in Czechia in the Sudetenland, where the German population was displaced after World War II. These regions, characterised by high depopulation rates, have significant tourism potential due to their rich natural and cultural resources. This study explores new directions in gamification and identifies successful examples in cultural heritage care. Using geospatial data, the research tests various gamification techniques in the field on the background of concepts STEM and HASS. The findings suggest that gamification is crucial for regional development and community engagement, leading to revitalising abandoned villages and economic diversification. The study highlights the importance of gamification in preserving cultural heritage and its role in regional development, education, and tourism. Rurex represents an innovative gamification process with significant potential for future development and sustainability.